Enzyme-Free Colorimetric Sensing of Glucose using Silver Nanoparticles with a Green Stabilizing Agent from Capsicum chinense Jacq Extract - Putra, Boyfannie Ivan; Sulistyarti, Hermin; Utama, Muhammad Mashuri; Haryanto, Aura Ananda; Retnowati, Rurini; Rafi, Mohamad; Sabarudin, Akhmad (UI Scholars Hub, 2025)
Diabetes mellitus (DM) is a significant global health issue characterized by abnormal glucose levels in the human body. DM diagnostics are often based on invasive sampling from blood, which poses a potential risk of infection and tissue damage. Therefore, a non-enzymatic and non-invasive method for glucose monitoring is demanded as a simple alternative to glucose detection in urine samples. In this work, enzyme-free glucose determination is based on the formation of silver nanoparticles stabilized by Capsicum chinense Jacq extract (CCJ-AgNPs). Under alkaline conditions, glucose functions as a reducing agent for silver ions, and the extract acts as a stabilizer to prevent agglomeration. The effect of reaction time, extract concentration, NaOH concentration, and AgNO3 concentration was studied to determine the optimum conditions for glucose sensing (reaction time: 5 min, extract volume: 2 mL, NaOH concentration: 0.05 M, and AgNO3 concentration: 0.2 mM). The linearity of glucose determination was obtained from 0 to 900 mg/L with LOD and LOQ of 1 and 5 mg/L, respectively. The proposed method demonstrated good selectivity against citric acid, NH4Cl, NaCl, H2PO4, and urea at a concentration of 100 mg/L, with good accuracy for the recovery test, ranging from 93.7% to 101.8%. This method can serve as an alternative approach for simple, non-invasive, and non-toxic glucose monitoring in human urine with high sensitivity and specificity.